ANALISIS PERHITUNGAN PPH 21 BERDASARKAN UNDANG-UNDANG PERPAJKAN PADA PT. BUMI LINTAS TAMA CABANG 21 - Djohariah Djohariah (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2016)
This study To determine procedures for application of income tax (VAT) of article 21 made by the company PT. Earth Cross Cab themes. Bone. In writing the lines, the author uses the comparative analysis method by comparing pph 21 according to the tax laws with 21 pph calculations by the company PT. Earth Cross Cab Scene, Bone. Dala results of this study in which the calculation of income tax (VAT) 21 according PT.Bumi Scene Cross compliance with the tax laws so that the hypothesis can be accepted, still there are some employees who have not registered as taxpayers or do not have a TIN, are reduction of tax payments year to year because of changes